2015
DOI: 10.1111/epp.12223
|View full text |Cite
|
Sign up to set email alerts
|

Invasion potential of Agrilus planipennis and other Agrilus beetles in Europe: import pathways of deciduous wood chips and MaxEnt analyses of potential distribution areas

Abstract: Bark‐ and wood‐boring beetles in the genus Agrilus (Coleoptera: Buprestidae) can survive wood‐chipping, and Agrilus planipennis has established in North America and European Russia with devastating impacts on forest ecosystems. The work presented in this paper combined import statistics of deciduous wood chips, Maximum entropy modelling (MaxEnt) of climatic similarities, and the distribution of potential tree hosts to predict the likelihood of four selected North American Agrilus species to become introduced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…The only attempt to predict the potential A. planipennis range in Europe by climatic variables was conducted using maximum entropy modelling [17]. This model has a number of serious flaws.…”
Section: Of 11mentioning
confidence: 99%
“…The only attempt to predict the potential A. planipennis range in Europe by climatic variables was conducted using maximum entropy modelling [17]. This model has a number of serious flaws.…”
Section: Of 11mentioning
confidence: 99%
“…Agrilus planipennis can tolerate high temperatures and shows remarkable thermal plasticity . Climatic conditions in the EU territory are generally not a limiting factor for EAB establishment and spread (VKM, 2014), and maximum entropy modelling (MaxEnt) shows a high environmental suitability overall for the EAB in Europe (Flø et al, 2015). Both mean temperatures and precipitation across Europe are suitable for the development of all life stages of the beetle, and there is not likely to be a climatic barrier to its establishment ( Figure 5).…”
Section: Climatic Suitabilitymentioning
confidence: 99%
“…Climate and distribution of susceptible host plants are critical factors considered in predicting the potential distributions of alien species including A. planipennis [12]. Several prognoses of the potential range in Europe based on different approaches have been made [13][14][15]. Since the main factor limiting A. planipennis distribution is host availability, a high-resolution map of A. planipennis invasion risk for southern central Europe (Austria, Switzerland, Liechtenstein, southern Germany) was based on the distribution of ash trees F. excelsior [13].…”
Section: Introductionmentioning
confidence: 99%
“…Since the main factor limiting A. planipennis distribution is host availability, a high-resolution map of A. planipennis invasion risk for southern central Europe (Austria, Switzerland, Liechtenstein, southern Germany) was based on the distribution of ash trees F. excelsior [13]. Another model based on the maximum entropy modelling (MaxEnt) used the combination of 19 climatic parameters has shown that the regions of Europe adjacent to the known range of A. planipennis are suitable for this species; therefore, the climatic factors would not prevent the spread to adjacent regions [14]. The prognosis based on the minimum winter temperature as a possible limiting factor has shown that low winter temperatures would not prevent the spread of A. planipennis in all regions of Europe, except some eastern districts of European Russia [15].…”
Section: Introductionmentioning
confidence: 99%